2019
DOI: 10.1186/s13063-018-3097-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a short video-based educational intervention on factors related to clinical trial participation in adolescents and young adults: a pre-test/post-test design

Abstract: BackgroundPoor clinical trial enrollment continues to be pervasive and is especially problematic among young adults and youth, and among minorities. Efforts to address barriers to enrollment have been predominantly focused on adult diseased populations. Because older adults may already have established attitudes, it is imperative to identify strategies that target adolescents and young adults. The purpose of this study was to test the effectiveness of an educational video on factors related to clinical trial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Our findings are supported by a recent systematic review, which found that health illiteracy and poor communication between health providers and AYA cancer patients are major barriers for CT enrollment 3 . Educational interventions, such as a short video with information about CTs, may increase AYAs willingness to learn about and participate in CTs 38 . Additionally, strategies to increase educational resources can help clinicians to better advise their patients about CTs 3 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings are supported by a recent systematic review, which found that health illiteracy and poor communication between health providers and AYA cancer patients are major barriers for CT enrollment 3 . Educational interventions, such as a short video with information about CTs, may increase AYAs willingness to learn about and participate in CTs 38 . Additionally, strategies to increase educational resources can help clinicians to better advise their patients about CTs 3 …”
Section: Discussionsupporting
confidence: 77%
“…3 Educational interventions, such as a short video with information about CTs, may increase AYAs willingness to learn about and participate in CTs. 38 Additionally, strategies to increase educational resources can help clinicians to better advise their patients about CTs. 3 Other hospital staff such as research nurses and clinical research coordinators are key to provide additional education on CTs for AYAs.…”
Section: Discussionmentioning
confidence: 99%
“…Short video educational tools have been shown to be effective in increasing receptivity to hearing about and participating in clinical trials in the healthy AYA population. 34 Although there are reports that AYAs perceive their inclusion in clinical trials may lead to improved quality of care 35 or that they participate for altruistic reasons, 10 only limited data suggest that CCT involvement actually leads to reduced quality of life. 36 Ensuring communication of accurate information about trials and that trials for AYAs minimize additional patient burden where allowed can address concerns about trials making "treatment more difficult" and "more trouble than standard care."…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, short videos, with their characteristics of simplicity, effectiveness, and ease of access and dissemination, had a significant and consistent impact on students' emotions in a nutrition education intervention [11]. Following that, the effectiveness of the intervention's effects on clinical education-related factors was also confirmed [12]. Furthermore, short videos, in addition to direct interventions during teaching, served as feedback interventions to assess students' learning situations [13].…”
Section: Introductionmentioning
confidence: 89%